GROSS MORPHOLOGY AND MORPHOMETRICAL STUDY OF FEMALE REPRODUCTIVE TRACT IN SIRUVIDAI CHICKEN DURING LAYING AND BROODINESS PHASE - J. Violet Beaulah; Geetha Ramesh; T.A. Kannan; O.R. Sathyamoorthy; R. Richard Churchil; V. Leela; P. Sridevi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Avian species reproduce sexually by the fusion of male and female gamete spermatogonia and oogonia-produced by differentiated testes and ovaries. Fertilization is internal and all birds are oviparous. Reproduction in birds entirely varies from other animals. The two essential reproductive organs ere the ovary and oviduct which were involved in the synthesis of egg in adult laying hen. Gross and morphometrical studies were carried out on the female reproductive tract in twelve Siruvidai chicken of which six at laying phase and six at broodiness phase. The birds were reared in Poultry Research Station, Madhavaram, Chennai-51. In laying phase, the left ovary showed mature ovarian follicles whereas the ovary during broodiness phase was in the form of a bunch of grapes with no hierarchical follicles. There was no significant difference in the body weight of the bird during laying and broodiness. The mean length, weight and width of ovary and oviduct had a highly significant difference during laying and broodiness phase. Gross morphology revealed that only the left female reproductive tract was well-developed both during laying and broodiness phase and the morphometric data analyzed will provide a baseline for subsequent studies and also for comparison with other avian species.